Spectrophotometric evaluation of staining of different types of light-cure composite resins after exposure with different light-cure intensities: An in vitro study - Pawar, Pawan Anil; Gulve, Meenal N; Aher, Gayatri B; Kolhe, Swapnil J; Pramaod, J (Journal of conservative dentistry, 2022)
Relation between the adequate intensity output of curing lights on color stability of composite resin is well accepted. To investigate the effect of different light-curing intensities and its relation to color stability of different polymerized composite resin materials using the spectophotometric analysis. Comparative study done on composite resin discs. A total of 180 discs comprising sixty discs prepared from three different composite resins, namely microhybrid composite resin (Filtek Z100,3M ESPE), nanohybrid composite resin (Filtek Z250 XT, 3M ESPE), and nanofilled composite resin (Filtek Z350 XT,3M ESPE) using three different light curing intensities, viz., 325-425 mW/cm , 750-850 mW/cm , and 1000-1100 mW/cm . Later these discs were stained with 2% methylene blue followed by re-absorption in absolute alcohol for supernatant solution preparation which is used for the spectrophotometric analysis. Spectrophotometric absorption values were analyzed using the one-way ANOVA test for intergroup analysis. Mean stain absorption was the highest with nanofilled composite resin (Filtek Z350 XT,3M ESPE) after exposure with light-curing intensity of 325-425 mW/cm and least with microhybrid composite resin (Filtek Z100, 3M ESPE) after exposure with light-curing intensity of 750-850 mW/cm and this difference found was highly significant statistically ( < 0.001). Microhybrid composite resin (Filtek Z100, 3M ESPE) cured with intensity of 750-850 mW/cm showed least stain absorption indication most color stability and esthetic function.